1999
DOI: 10.1034/j.1398-9995.1999.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment in five cases of allergic reactions due to gastroallergic anisakiasis

Abstract: In gastroallergic anisakiasis, the antigens of the live parasite probably cause the allergic symptoms. Patients with this disease can tolerate deep-frozen seafood, in which the parasites are dead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
(2 reference statements)
2
24
0
1
Order By: Relevance
“…2). This result supports the previous finding (Alonso et al 1999;Alonso-Gomez et al 2004) that the ingestion of frozen fish is safe in anisakiasis. Combining the data presented in Figs.…”
supporting
confidence: 83%
“…2). This result supports the previous finding (Alonso et al 1999;Alonso-Gomez et al 2004) that the ingestion of frozen fish is safe in anisakiasis. Combining the data presented in Figs.…”
supporting
confidence: 83%
“…Indeed, on the basis of previous reports (9,27), it could be argued that in addition to Anisakis infections, CAP FEIA detects IgE antibodies induced by free Anisakis allergens that are present in fish contaminated with this parasite and categorizes the patients as positive. However, this hypothesis appears unlikely, considering the negative results obtained in provocation test studies carried out on sensitized patients, using frozen (1,2,14), freeze-dried (32), or excretory-secretory (6) antigens, as well as in experiments conducted in a murine model of anaphylaxis (7). In consequence, it appears more likely that the large number of positive results obtained with CAP FEIA is the result of the detection of IgE antibodies induced by other allergens that share common epitopes with Anisakis allergens, as previously reported (15,18,29).…”
Section: Discussionmentioning
confidence: 94%
“…The risk of allergic reactions after nonviable anisakids fish ingestion is a matter of some concern. Some authors reported that sensitized subjects did not show any symptom after administration of dead larvae (Alonso-Gómez et al, 2004;Sastre et al, 2000;Alonso et al, 1999). On the contrary, other researchers showed that 13 of 64 subjects with Anisakis sensitization history had adverse reaction after eating properly (Moneo et al, 2007).…”
Section: Introductionmentioning
confidence: 94%